2021
DOI: 10.1002/jsfa.11569
|View full text |Cite
|
Sign up to set email alerts
|

Candelilla wax‐based oleogels versus palm oil: evaluation of physical properties of innovative and conventional lipids using optical techniques

Abstract: BACKGROUND: The widespread use of palm oil in food production affects high consumption of long-chain saturated fatty acids, which increases the risk of cardiovascular disease. Solid or semi-solid wax-based oleogels obtained as a result of edible oils structuring can be an alternative.RESULTS: Oleogels, obtained by structuring a mixture of refined rapeseed and linseed oils (1:1) with 30-80 g kg −1 candelilla wax (CW), were investigated using optical techniques: multi-speckle diffusing wave spectroscopy, centrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…For example, it was shown that increasing the cooling rate positively affects the oleogel firmness. Similar changes are also observed for the oleogel microstructure, particularly in decreasing the crystal size [ 7 , 8 , 9 , 10 ]. Despite a considerable number of articles on the study of the structure and physical properties of oleogels, there is still no common physically substantiated understanding of the relationship between structure and properties of wax-based oleogels.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, it was shown that increasing the cooling rate positively affects the oleogel firmness. Similar changes are also observed for the oleogel microstructure, particularly in decreasing the crystal size [ 7 , 8 , 9 , 10 ]. Despite a considerable number of articles on the study of the structure and physical properties of oleogels, there is still no common physically substantiated understanding of the relationship between structure and properties of wax-based oleogels.…”
Section: Introductionsupporting
confidence: 69%
“…A positive linear relationship between 1/ and 1/ observed for the BW oleogel ( Figure 3 a) is an expected outcome that might be observed for other systems [ 16 ]. Also, the same trend is expected for wax-based oleogels, since the smaller their crystals are in size, the more homogeneous they are distributed [ 8 ]. However, as shown in Figure 3 b, this relationship is still linear but negative for the BWH oleogel.…”
Section: Resultsmentioning
confidence: 53%
“…Analysis of microscopic images of crystals developed in oleogels allows for preliminary detection and identification of oleogelators [ 20 ]. Another optical technique which measures light transmission and scattering by the sample provides important information on microrheological properties of the tested samples [ 21 ]. Usually, the rheological test makes measurements on the macroscopic scale and damages samples.…”
Section: Introductionmentioning
confidence: 99%
“…The MS-DWS method tracks changes in particle motion under the influence of thermal energy in real time (through dynamic light scattering). The advantage of the passive optical microrheology technique is its low invasiveness, and the same sample can be again used for analysis [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation